Protection Of The Parties In The Implementation Of The Ship Lease Agreement (Case Study Decision No.231 / Rev.G / 2020 / PN.JKT.UTR) - Al-Hafiz Al-Hafiz; Kusbianto Kusbianto; Ariman Sitompul (International Asia Of Law and Money Laundering (IAML), 2023)
The mechanism of transfer of rights in the lease agreement can be done with several stages, namely: the transfer of rights to an object must be accompanied by the delivery of the object. Surrender in the process of handing over property rights cannot be done carelessly regardless of the law that regulates it. Deed of lease made by and before a notary. Settlement of disputes over the sale and purchase agreement of the ship can be done by: non-litigation dispute resolution i.e. settlement out of court by means of abritrase, negotiation, mediation, conciliation, expert assessment. Dispute resolution in court (litigation) is the process of dispute resolution in court all parties in dispute face each other to defend their rights in court by filing a civil lawsuit.. Based on decision number 231 / Pdt.G / 2020 / PN.Jkt.Utr legal protection provided that the parties can file a civil lawsuit to the court where the parties in dispute are PT.Indoraya Makmur Energi (Hamad Siri) as the plaintiff with Rachman Saleh (PT.Timas Merak) as the defendant in the decision of the case the judge has provided legal protection where: stating the defendant has defaulted to the plaintiff. Punish the defendant to pay the rent for the SPOB Pulomas 7 ship for 11 months starting from June 11, 2019 to May 11, 2020, which is Rp. 450,000,000 x 11 months = Rp. 4,950,000,000 (four billion nine hundred and fifty million rupiah).